Comparative Proteomic Analysis Reveals the Upregulation of Ketogenesis in Cardiomyocytes Differentiated from Induced Pluripotent Stem Cells. Issue 7 (26th February 2019) - Kim, Sunjoo; Jeon, Ju Mi; Kwon, Oh Kwang; Choe, Mu Seog; Yeo, Han Cheol; Peng, Xiaojun; Cheng, Zhongyi; Lee, Min Young; Lee, Sangkyu
Abstract: Diverse metabolic pathways, such as the tricarboxylic acid cycle, pyruvate metabolism, and oxidative phosphorylation, regulate the differentiation of induced pluripotent stem cells (iPSCs) to cells of specific lineages and organs. Here, the protein dynamics during cardiac differentiation of human iPSCs into cardiomyocytes (CMs) are characterized. The differentiation is induced by N ‐(6‐methyl‐2‐benzothiazolyl)‐2‐[(3, 4, 6, 7‐tetrahydro‐4‐oxo‐3‐phenylthieno[3, 2‐d]pyrimidin‐2‐yl)thio]‐acetamide, a Wnt signaling inhibitor, and confirmed by the mRNA and protein expression of cTnT and MLC2A in CMs. For comparative proteomics, cells from three stages, namely, hiPSCs, cardiac progenitor cells, and CMs, are prepared using the three‐plex tandem mass tag labeling approach. In total, 3970 proteins in triplicate analysis are identified. As the result, the upregulation of proteins associated with branched chain amino acid degradation and ketogenesis by the Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis are observed. The levels of 3‐hydroxymethyl‐3‐methylglutaryl‐CoA lyase, 3‐hydroxymethyl‐3‐methylglutaryl‐CoA synthase 2, and 3‐hydroxybutyrate dehydrogenase 1, involved in ketone body metabolism, are determined using western blotting, and the level of acetoacetate, the final product of ketogenesis, is higher in CMs. Taken together, these observations indicate that proteins required for the production of diverse energy sources are naturally self‐expressed during cardiomyogenic differentiation. Furthermore, acetoacetate concentration might act as a regulator of this differentiation.